2016
DOI: 10.1103/physrevlett.117.173602
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics and Strong Cavity Cooling of Levitated Nanoparticles

Abstract: Optomechanical systems explore and exploit the coupling between light and the mechanical motion of matter. A nonlinear coupling offers access to rich new physics, in both the quantum and classical regimes. We investigate a dynamic, as opposed to the usually studied static, nonlinear optomechanical system, comprising of a nanosphere levitated and cooled in a hybrid electro-optical trap. An optical cavity offers readout of both linear-in-position and quadratic-in-position (nonlinear) light-matter coupling, whils… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 33 publications
(41 reference statements)
5
151
0
Order By: Relevance
“…This will necessitate involving a non-Gaussian element in the network, whether taking advantage of a non-Gaussian measurement, a non-linear optomechanical dynamics, or an already prepared nonGaussian resource. Promisingly in this direction, it has been shown that opto-and electro-mechanical systems can intrinsically host non-linearities in various settings [33,36,76,77], and this possibility has been suggested for engineering non-Gaussian states, dynamics, and measurements [32,[78][79][80][81][82][83][84][85]. The latter could potentially be exploited to unlock the universality of computation and this shall be the topic of future work.…”
Section: Discussionmentioning
confidence: 99%
“…This will necessitate involving a non-Gaussian element in the network, whether taking advantage of a non-Gaussian measurement, a non-linear optomechanical dynamics, or an already prepared nonGaussian resource. Promisingly in this direction, it has been shown that opto-and electro-mechanical systems can intrinsically host non-linearities in various settings [33,36,76,77], and this possibility has been suggested for engineering non-Gaussian states, dynamics, and measurements [32,[78][79][80][81][82][83][84][85]. The latter could potentially be exploited to unlock the universality of computation and this shall be the topic of future work.…”
Section: Discussionmentioning
confidence: 99%
“…The r-heterodyne technique may also have further practical applications for optomechanical systems with non-stationary cavity dynamics [26][27][28].…”
Section: Fig 1: (A)mentioning
confidence: 99%
“…The amplitude of the micromotion is proportional to the Paul trap voltage, the number of charges on the particle and the well number N. Cavity cooling of a nanoparticle in the hybrid trap has been demonstrated. 1,3 There are a number of important improvements that are required to reach the ground state. These include improvements in the Paul trap as well as the reduction of the major noise sources.…”
Section: Cooling Mechanismmentioning
confidence: 99%
“…The particle-light coupling is highly nonlinear and both linear and quadratic couplings have been reported. 1 The particle micromotion in the Paul trap at the drive frequency ω d leads to some excursion of the particle away from the antinode where there is a non vanishing linear optomechanical coupling. The amplitude of the micromotion is proportional to the Paul trap voltage, the number of charges on the particle and the well number N. Cavity cooling of a nanoparticle in the hybrid trap has been demonstrated.…”
Section: Cooling Mechanismmentioning
confidence: 99%